Determinants of Hand Hygiene Practice at Critical Times among Food Handlers in Educational Institutions of the Sagnarigu Municipality of Ghana: A Cross-Sectional Study - Kingsley E Amegah; Henry O Addo; Mary E Ashinyo; Loveland Fiagbe; Serene Akpanya; Samuel K Akoriyea; S Dajan Dubik (SAGE Publishing, 2020)
Introduction: Food handlers' hands serve as a vehicle for potential foodborne pathogenic contamination which constitutes a public health risk. In Ghana, there are always constant reports of outbreaks of foodborne diseases in schools. However, determinants of hand hygiene practice among educational institutions food handlers are little known. The study, therefore, aimed to assess the determinants of hand hygiene practice at critical times among educational institutions' food handlers in the Sagnarigu Municipality of Ghana. Methods: This was a cross-sectional survey among educational institutions food handlers in the Sagnarigu Municipality. Two hundred and six food handlers were selected through convenience sampling in the educational institutions. At the same time, structured questions that were developed from previous studies were used to assess food handlers' hand hygiene practice at critical times. Data were analyzed using descriptive statistics, bivariate and multivariate logistic regression models. All variables with their respective confidence intervals (95%) and adjusted odds ratios were declared significant at P -values less than .05. Results: Hand hygiene practice at critical times among the food handlers were relatively good at a rating of 66.0% (95% CI: 59.1, 72.5%). Good hand hygiene practice at critical times was less likely among food handlers with no food safety training (AOR 0.04; 95% CI: 0.00, 0.41) and food handlers who had insufficient knowledge of hand hygiene (AOR 0.06; 95% CI 0.01, 0.25). Good hygiene practice at critical times was 99% lower in food handlers with a negative attitude as compared to food handlers with positive attitudes towards hand hygiene at critical times (AOR 0.01; 95% CI 0.00, 0.07). Only 17.0% of the food handlers demonstrated proper handwashing techniques, whereas a good number (85.4%) of the food handlers did not wash their hands after touching money. Conclusion: Good hand hygiene practice at critical times was relatively good. Food safety training, knowledge of hand hygiene and attitudes towards hand hygiene were independent predictors of hand hygiene practice at critical times. Concerned stakeholders and organizations should focus on WASH interventions that seek to improve educational institutions food handlers' knowledge and attitudes towards hand hygiene, coupled with training on food safety.